2014
DOI: 10.1017/s0007485314000182
|View full text |Cite
|
Sign up to set email alerts
|

A case of ecological specialization in ladybirds:Iberorhyzobius rondensis(Coleoptera: Coccinellidae), potential biocontrol agent ofMatsucoccus feytaudi(Hemiptera: Matsucoccidae)

Abstract: Specialization is an important attribute of a biological control agent. The maritime pine bast scale, Matsucoccus feytaudi Ducasse (Hemiptera Matsucoccidae), is an invasive species in Southeast France and the North of Italy. Iberorhyzobius rondensis Eizaguirre (Coleoptera: Coccinellidae), is a recently described ladybird species. Both adults and larvae are predaceous, feeding on egg masses of M. feytaudi, and are strongly attracted to M. feytaudi's sex pheromone. To evaluate the potential of I. rondensis as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Our study showed that the habitat specialists could temporarily switch to preying on invertebrates that are unsuitable or disregarded by competitors. Close habitat and prey specializations, as reported for Iberorhyzobius rondensis that exclusively occurs on Pinus pinaster and preys on Matsucoccus feytaudi (Tavares et al, 2014), are probably very rare among predatory ladybirds. Table S1.…”
Section: Discussionmentioning
confidence: 71%
“…Our study showed that the habitat specialists could temporarily switch to preying on invertebrates that are unsuitable or disregarded by competitors. Close habitat and prey specializations, as reported for Iberorhyzobius rondensis that exclusively occurs on Pinus pinaster and preys on Matsucoccus feytaudi (Tavares et al, 2014), are probably very rare among predatory ladybirds. Table S1.…”
Section: Discussionmentioning
confidence: 71%
“…Comments. This is an endemic species of the Iberian Peninsula, associated with maritime pine forests, and is a specialist predator of the maritime pine bast scale, Matsucoccus feytaudi Ducasse (Tavares et al 2014;Tavares et al 2015a;Tavares et al 2015b). Adults and mostly larvae were shown to be attracted by the sex pheromone of their prey (Branco et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Lady beetles, ladybugs, or ladybird beetles (Coccinellidae) and their larvae feed on soft-bodied arthropods such as aphids, mealybugs, scales, whiteflies (Hemiptera), and mites (Arachnida) (Obrycki and Kring 1998), among others. Because of their diet, they are widely used as biocontrol agents in diverse ecosystems from agricultural to forests (Obrycki and Kring 1998;Tavares et al 2014). In Puerto Rico, the lady beetle fauna consists of 53 described species, seven of which have been introduced as biological control agents (Segarra-Carmona et al 2021).…”
mentioning
confidence: 99%